ADAPTIVE MOTION ESTIMATION ALGORITHM FOR CROWDED SCENES - KAJO, IBRAHIM (2014)
The motion estimation in video pictures has attracted a great deal of interest in computer vision. For crowd analytics and surveillance systems, motion estimation is an indispensable first-step. Lots of crowd motion estimation algorithms have been presented in the last years comprising pedestrian motion. Most of this method depends on optical flow and background subtraction. Several areas, such as evacuation movements, pedestrian movements at transit stations and local interaction behavior, were studied. However, algorithms based on optical flow and background subtraction cannot estimate themotion in real timeespecially in crowded scenes.